Antithrombotic Properties of Dermatan Sulphate (MF 701) in Haemodialysis for Chronic Renal Failure - Ryan, K E; Lane, D A; Flynn, A; Ireland, H; Boisclair, M; Shepperd, J; Curtis, J R (Thrombosis and Haemostasis, 1992)
The therapeutic potential of the glycosaminoglycan (GAG), dermatan sulphate (DS), as an antithrombotic agent in humans has yet to be established. We have performed dose ranging studies of DS to determine its effectiveness as an antithrombotic agent in patients (n = 6–8) undergoing haemodialysis for chronic renal failure. In an initial study, Study 1, i.v. bolus doses of 2–4 mg/kg and 5–6 mg/kg DS were given to patients dialysing with polyacrylonitrile hollow fibre (PAN HF) membranes. In a second crossover study, Study 2, performed using cuprophane hollow fibre (CHF) membranes, i. v. bolus doses of 3 mg/kg and 6 mg/kg DS were compared to a standard unfractionated heparin (UFH) regime that has been shown previously to inhibit fibrin formation. Further infusion studies, Study 3 and Study 4 evaluated the antithrombotic efficacy of an i. v. DS bolus of 3 mg/kg plus an i. v. infusion of DS 0.6 mg kg-1 h-1 and a DS bolus of 5 mg/ kg plus an infusion of 1 mg kg-1 h-1 over 5 h, respectively. These studies were compared to standard UFH regimes in a randomised crossover design. Plasma levels of fibrinopeptide A (FPA) and thrombin-antithrombin (TAT) were used as markers of fibrin formation and thrombin generation during dialysis using both membranes.The changes in DS concentration following administration of the different doses were similar in Studies 1 and 2. However, the effectiveness of DS as an anticoagulant appeared to depend markedly on the different dialyser types used in the two studies. In Study 1, 13/14 dialyses required additional UFH to complete a normal ~6 h session and DS was unable to prevent thrombin and fibrin formation, as determined by measurement of plasma FPA and TAT. However, some dose related effects were observed in the levels of these markers. Furthermore, DS levels correlated with those of FPA and TAT. In Study 2, increasing doses of DS (3 mg/kg and 6 mg/kg), allowed longer dialysis sessions (mean 4.57 h c.f. 5.25 h), approaching that obtained with UFH regime (5.86 h). FPA and TAT generation were incompletely suppressed by both doses of DS; FPA rose significantly compared to that observed with the UFH regime, while TAT did not. While no significant differences in the activation markers were observed between the two DS doses, DS levels, taken as a whole, showed significant negative correlations with those of FPA and TAT Little effect on the KCCT was seen.In Study 3, 3/6 patients required additional UFH (mean dialysis duration with DS 4.33 h c. f. 5.67 h with UFH). Mean DS levels were maintained between 35–40 µg/ml. Mean plasma FPA levels were maintained at constant levels throughout dialysis following DS administration but were higher than those observed following the UFH regime. In Study 4 mean DS levels were